PD-1 Blockade Restores the Proliferation of Peripheral Blood Lymphocyte and Inhibits Lymphocyte Apoptosis in a BALB/c Mouse Model of CP BVDV Acute Infection - Liu, Yu; Wu, Chenhua; Chen, Nannan; Li, Yang; Fan, Chunling; Zhao, Shangqi; Bai, Tongtong; Zhao, Zhibo; Chen, Jinwei; Su, Siyu; Zhang, Zecai; Zhou, Yulong; et al. (Frontiers in Immunology, 2021)
Acute infection of bovine viral diarrhea virus (BVDV) is associated with immune dysfunction and can cause peripheral blood lymphopenia and lymphocyte apoptosis. Our previous study has confirmed that programmed death-1 (PD-1) blockade inhibits peripheral blood lymphocyte (PBL) apoptosis and restores proliferation and anti-viral immune functions of lymphocytes after BVDV infection in vitro. However, the situation in vivo remains to be further studied and confirmed. Therefore, in this study, we established a BALB/c mouse model of acute BVDV infection with cytopathic (CP) BVDV (strain NADL) and non-cytopathic (NCP) BVDV (strain NY-1). Then, we examined the mRNA and protein levels of PD-1 and programmed death-ligand 1 (PD-L1) in peripheral blood mononuclear cells (PBMC) from BVDV-infected mice and analyzed the effects of PD-1 blockade on the proportions of CD3+, CD4+, and CD8+ T cell subsets, the apoptosis and proliferation of PBL, and the production of IL-2 and IFN-γ. We found that leukopenia, lymphocytopenia, and thrombocytopenia were developed in both CP and NCP BVDV-infected mice at day 7 of post-infection. The mRNA and protein expression of PD-1 and PD-L1 were significantly upregulated in CP and NCP BVDV-infected mice. Moreover, PD-1/PD-L1 upregulation was accompanied by leukopenia and lymphopenia. Additionally, PD-1 blockade inhibited PBL apoptosis, restored the proportions of CD3+, CD4+, and CD8+ T cell subsets, and increased IFN-γ production in BVDV-infected mice. However, blocking PD-1 did not significantly affect PBL proliferation and IL-2 production in NCP BVDV-infected mice. Our findings further confirmed the immunomodulatory role of PD-1 in peripheral blood lymphocytopenia in vivo and provided a scientific basis for exploring the molecular mechanism of immune dysfunction caused by acute BVDV infection.